2009
DOI: 10.1136/adc.2008.142869
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis in premature and term children

Abstract: The prevalence of AD in the first 2 years of life was 18.6%, with no significant difference between preterm and term children. Adverse reactions to food were found in 15.8% (a similar prevalence in premature and term children). Mode of delivery did not affect prevalence of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 17 publications
3
25
0
1
Order By: Relevance
“…Indeed, some studies found that a low GA was associated with reduced risk of AD [9][10][11] or atopy, 17 while others reported low GA to be linked to a higher risk of AD 8 or atopy. [12][13][14]17 Direct comparisons between these studies are difficult, due to variation in study designs, AD definitions and study populations. [12][13][14]17 Direct comparisons between these studies are difficult, due to variation in study designs, AD definitions and study populations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies found that a low GA was associated with reduced risk of AD [9][10][11] or atopy, 17 while others reported low GA to be linked to a higher risk of AD 8 or atopy. [12][13][14]17 Direct comparisons between these studies are difficult, due to variation in study designs, AD definitions and study populations. [12][13][14]17 Direct comparisons between these studies are difficult, due to variation in study designs, AD definitions and study populations.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of food allergy in this cohort was 4.2%, and no significantly increased risks were found for food allergy development from birth to 7 years of age for either prematurity or low birth weight. In Norway, Kvenshagen et al [37] found that there was no difference in the prevalence of eczema/atopic dermatitis at 2 years of age between 32/161 (19.9%) children born preterm and 63/351 (17.9%) born at term. Adverse reactions to food were found in 15.8% of children with atopic dermatitis, with a similar prevalence in children born preterm (15.6%) compared with those born at term (15.9%).…”
Section: Possible Harms Of An Early Introduction Of Solid Foodsmentioning
confidence: 99%
“…The atopic predisposition of preterm infants might differ from that of term infants and this predisposition may vary for different allergic diseases such as atopic dermatitis and asthma 34–38 . In a recent study, Kvenshagen et al 39 . found no difference in the prevalence of atopic dermatitis between preterm and term infants.…”
Section: Cytokine Responsesmentioning
confidence: 97%